Microscopic Characterization of Optimized Particleboards Made from Softwood Sawdust and Rice Husk Using Optimized Polystyrene Waste Adhesive - HAMIDU, Lucas A. J. (FUDMA Journal of Engineering and Technology, 2026)
Increased safety concerns in the manufacturing of particleboards require intensive investigation of the possible composition of elements and oxides present. In this work, already optimized particleboards made from softwood sawdust (OSDP) and rice husk (ORHP) using optimized Ri7Adh2 adhesive were characterized, via scanning electron microscope-energy dispersive spectroscope (SEM-EDX) and X-ray fluorescent spectroscope (XRF) instrumentations to ascertain the elements and oxides compositions present. The OSDP and ORHP samples were conditioned, coated with gold before analysis to obtain a complete image. The image was obtained in a wide range of 200 µm with the sputter coater Q150T UK model and recorded with a resolution of 15 keV to detect the elements present in the samples. XRF investigations were performed according to ASTM D6052 – 97. The scanning electron microscope (SEM) results showed a homogenized phase with adequate mixing between the softwood sawdust and optimized Ri7Adh2 adhesive, while the EDX results showed 16 elements and 21 oxides from the XRF spectrum for the OSDP. The ORHP results also showed a homogenized phase with adequate Ri7Adh2 adhesive embedded in the rice husk matrix, with the results showing EDX 16 elements and XRF 22 oxides compositions. These assessments showed that the results of particleboards made from the spectra of optimized particleboards (OSDP and ORHP) are emission-free and safe for indoor use.
Keywords: Adhesive, Active component, Particleboard, Scanning electron microscope, X-ray fluorescent.